Iraq : Staff Report for the 2009 Article IV Consultation and Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2009 Article IV Consultation highlights that Iraq's longer-term economic outlook is strong as oil prices and production are projected to increase markedly in the coming years. However, based on conservative oil price assumptions, the external current account and the overall balance of payments are expected to remain in deficit in 2010 and 2011. Similarly, Iraq's fiscal position is projected to record significant, albeit declining deficits in both years, before returning to a surplus position in 2012.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet